2008
DOI: 10.1016/j.ijpsycho.2007.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Interhemispheric differences of spectral power in expressive language: A MEG study with clinical applications

Abstract: In the last decade we have seen an exponential growth of functional imaging studies investigating multiple aspects of language processing. These studies have sparked an interest in applying some of the paradigms to various clinically relevant questions, such as the identification of the cortical regions mediating language function in surgical candidates for refractory epilepsy. Here we present data from a group of adult control participants in order to investigate the potential of using frequency specific spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
45
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 58 publications
9
45
1
2
Order By: Relevance
“…The late time window, extending past the end of the analyzed epoch, and the central distribution of this effect point to a response-related explanation. Beta desynchronization over central channels has often been linked to motor preparation and imagery, both of limbs (De Lange, Jensen, Bauer, & Toni, 2008) and of speech (Piai, Roelofs, & Maris, 2014;Fisher et al, 2008), and has been shown to increase with response certainty (Alegre et al, 2004). Given that untrained novel words did not activate a representation based on which a response could be prepared, but existing words did, the larger desynchronization response to untrained existing versus novel words may reflect selective motor preparation for the existing words.…”
Section: Discussionmentioning
confidence: 99%
“…The late time window, extending past the end of the analyzed epoch, and the central distribution of this effect point to a response-related explanation. Beta desynchronization over central channels has often been linked to motor preparation and imagery, both of limbs (De Lange, Jensen, Bauer, & Toni, 2008) and of speech (Piai, Roelofs, & Maris, 2014;Fisher et al, 2008), and has been shown to increase with response certainty (Alegre et al, 2004). Given that untrained novel words did not activate a representation based on which a response could be prepared, but existing words did, the larger desynchronization response to untrained existing versus novel words may reflect selective motor preparation for the existing words.…”
Section: Discussionmentioning
confidence: 99%
“…In the present paper, we focus on the parallel between production and prediction in language, based on the dynamic principles of forward modeling a motor command. Given the relevance of beta band activity in the motor domain and the importance of motor planning for articulation, it is not surprising to observe that a number of studies have reported beta band effects related to speech production (Fisher et al, 2008;Singh, Barnes, Hillebrand, Forde & Williams, 2002). Recently, Findlay et al (2012) employed a verb generation task in which participants were presented with a noun and had to produce a related verb.…”
Section: Oscillatory Dynamics Reflecting Preparation For Articulationmentioning
confidence: 99%
“…1,5 Consequently, inconclusive results are reported in most patients younger than age 10 for ESM (up to 81%) and for IAT (50%). 5,6 In the past decade, noninvasive neuroimaging techniques, including functional magnetic resonance imaging (fMRI) [7][8][9][10][11] and magnetoencephalography (MEG), [12][13][14][15][16][17][18] have been widely used for language cerebral lateralization and mapping in adults and children. These techniques show very good concordance with invasive procedures (IAT and ESM) for language dominance and localization.…”
Section: Introductionmentioning
confidence: 99%